Spatial Ability Stress Test for Screening and Selection: The Development of SCOUT-R. (December 2020) - Brown, Noelle L.; Sibley, Ciara; Foroughi, Cyrus K.; Coyne, Joseph T.; Herdener, Nathan; Phillips, Henry; King, Kenneth
Spatial abilities are often predictive of occupational success. Specifically, they are thought to play a role in aviator success and thus, are evaluated in Naval and Air Force aviation selection. However, the selection process only includes a single assessment of spatial ability which recent findings have called into question its validity. The creation of a speeded spatial ability stress test with face validity for the Navy and Marine Corps aviation community was investigated. We developed SCOUT-R, a multitask environment where participants quickly discriminated target objects from distractors, all of which could appear in any 90° orientation. The results showed the speeded presentation affected subjective workload and task strategy; however, target discrimination improved as the speed of presentation increased. The implications for SCOUT-R as a spatial ability selection test are considered.